Practical guide for the comparison of two next-generation sequencing systems for solid tumour analysis in a universal healthcare system. Issue 3 (31st January 2018) - Maxwell, Perry; Hynes, Seán O; Fuchs, Marc; Craig, Stephanie; McGready, Claire; McLean, Fiona; McQuaid, Stephen; James, Jacqueline; Salto-Tellez, Manuel
Abstract : Aims: Although there have been excellent reports in the literature of validating next-generation sequencing, comparisons between two systems are not often published due to cost and time. We set out to establish that targetable mutations could be reliably detected with different gene panels and different chemistries using a common bioinformatics pipeline for meaningful comparisons to be made. Methods: After running selected formalin-fixed, paraffin-embedded samples through QPCR, Sanger sequencing and the 50 gene hotspot v2 panel from Life Technologies to determine standard-of-care variants, we compared the Oncomine panel from Life Technologies performed on a Personal Genome Machine (PGM) and the eight-gene actionable panel from Qiagen performed on a MiSeq platform. We used a common bioinformatics program following the creation of respective VCF files. Results: Both panels were accurate to above 90%, the actionable panel workflow was easier to perform but the lowest effective starting DNA load was obtained on the Oncomine workflow at 4 ng. Such minimal DNA can help with samples where there is limited material such as those for lung cancer molecular studies. We also discuss gene panel content and propose that increasing the gene profile of a panel will not benefit clinical laboratories where standard-of-care testing is all that is required. Conclusions: Once recognised, it may be cost-effective for such laboratories to begin validation with an appropriate bioinformatics pipeline for targeted multigene hotspot molecular testing.